COMPLEMENTARY THERAPY IN IMPROVING THE SLEEP QUALITY OF HEMODIALYSIS PATIENTS: A SCOPING REVIEW - Mesya, M; Permana, Iman (Universitas Aisyah Pringsewu, 2024)
Complementary therapy can be used as an alternative in treating sleep disturbance among hemodialysis patients. This study intends to pinpoint certain complementary treatment approaches that can enhance hemodialysis patients' sleep quality using Scooping Review. The databases Scopus, Proquest, PubMed, and ScientDirect are the ones that are monitored. The search terms to employ are